Local perception and knowledge of changing Alpine pastures - Vršnik, Elizabeta (Anthropological notebooks, 2022)
Alpine pastures are places in the Alps intended for grazing livestock during the warmer months of the year. Those in the Solčava region and more broadly in the Alpine area have been undergoing transformations due to the interrelation between geophysical, social and cultural changes in the landscape. Based on fi eld work in the Solčava region, this article explores the changes most often recognized by their owners and/or caretakers in the Alpine pastures of the village, and is an attempt to show how those changes are perceived and experienced by them. The specific understanding of the changes and the way the Alpine pastures are cared for are a result of distinct local perceptions, wherein knowledge, its attaining and intergenerational transmission have special significance.
Keywords: Alpine pastures; Alps; domačinski pogled; ethnology; Etnologija; gorski pašniki; landscape change; local knowledge; local perception; medgeneracijski prenos znanja; pašne planine; Savinjske Alpe; Slovenia; Solčava; Solčava region; spreminjanje krajine; transgenerational transmission of knowledge